Pemanfaatan Nira Batang, Bagas, dan Biji Sorgum Manis sebagai Bahan Baku Bioetanol - Pabendon, Marcia B.; Sarungallo, Rosalia S.; Mas’ud, S. (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
The study was conducted at ICERI (Indonesian Cereals Research Institute), at the Laboratory of Chemical Engineering, Paulus Christen University (UKIP), and at Laboratory of Bioprocess, Department of Chemical Engeneering, Polytechnic Ujung Pandang, from March to November 2010. The aim of this study was to determine the potential ethanol production derived from juice, bagasse (sellulose), and sorghum grain (starch). Eleven sweet sorghum genotypes were tested, local varieties Selayar Hitam, Sorgum Hitam, and variety Numbu were used as checks. The results showed that yield of stem biomass, high brix sugar content, high yield of bagasse, high grain yield, and high content of glucose derived from grain were characters that could be used as criteria for selection of sorghum genotypes producing high ethanol per unit area. These characters were correlated with the ethanol production per unit area. Genotypes 1521A, 15011A, and Watar Hammu Putih were prospective sweet sorghum for the ethanol production. These genotypes were supported by high yield of stem biomass per unit area, high brix sugar content, and high grain yield than check varieties, except for Watar Hammu Putih. Although all of the three raw materials had the potential use for bioethanol production, stem juice and bagasse were more suitable to be used than the grain, since it would not compete with the use of grain for food.